Pengembangan Media Permainan Tradisional Engklek pada Mapel IPAS Fase B di Jenjang Sekolah Dasar - Muayyad, Abdullah Nashih; Faradita, Meirza Nanda; Wahyuni, Holy Ichda (Universitas Nusantara PGRI Kediri, 2025)
Monotonous learning methods, confusing curriculum, lack of student motivation and low academic achievement of students. The teacher's task is very vital in fostering student motivation by creating interesting and meaningful learning. One of the media that can be used in the learning process is the traditional engklek game media. This study aims to develop traditional engklek game media that meets the criteria of valid, practical, and effective in phase B science learning at elementary school level. The type of research used is research and development (R&D) with the ADDIE model consisting of 5 stages, namely Analysis, Design, Development, Implementation, Evaluation. At the Development stage, the researcher conducted a validity test by two material experts and two media experts showing that this media is very valid, with a percentage of 97% from material experts and 96% from media experts. At the Implementation stage, the researcher conducted a practicality test assessed through student and teacher responses, resulting in a score of 84% from students and 89% from teachers. At the Evaluation stage, the researcher tested the effectiveness of the media as measured by student learning outcomes, which showed a percentage of 72%, indicating that the media was effectively used. Based on the results of the study, it can be concluded that the hopscotch game media is very feasible from the valid, practical, and effective aspects as a learning media in improving student learning outcomes.